2018
DOI: 10.1140/epjc/s10052-018-6163-8
|View full text |Cite|
|
Sign up to set email alerts
|

Operation of a ferromagnetic axion haloscope at $$m_a=58\,\upmu \mathrm {eV}$$ m a = 58 μ eV

Abstract: Axions, originally proposed to solve the strong CP problem of quantum chromodynamics, emerge now as leading candidates of WISP dark matter. The rich phenomenology associated to the light and stable QCD axion can be described as an effective magnetic field that can be experimentally investigated. For the QUAX experiment, dark matter axions are searched by means of their resonant interactions with electronic spins in a magnetized sample. In principle, axion-induced magnetization changes can be detected by embedd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…In order to maximise the axion induced signal in a realistic detector, it is important to shift from a single spin system to a system with a very high spin number. This number of spins is maximised in ferromagnetic crystals, particularly Yttrium Iron Garnet (YIG), that have been proposed as the core sensing element in previous proposals 25,26,28 . In addition to this, high quality YIG is characterised by relatively narrow linewidths that makes it a popular choice for research in the field of hybrid quantum system for future quantum information processing [34][35][36][37][38][39] .…”
Section: B Ferromagnetic Haloscopesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maximise the axion induced signal in a realistic detector, it is important to shift from a single spin system to a system with a very high spin number. This number of spins is maximised in ferromagnetic crystals, particularly Yttrium Iron Garnet (YIG), that have been proposed as the core sensing element in previous proposals 25,26,28 . In addition to this, high quality YIG is characterised by relatively narrow linewidths that makes it a popular choice for research in the field of hybrid quantum system for future quantum information processing [34][35][36][37][38][39] .…”
Section: B Ferromagnetic Haloscopesmentioning
confidence: 99%
“…It should be noted that this experiment being a directional detector of the axion dark matter field makes it also sensitive to the so called 'dark matter hurricane' or S1 stream which provides an additional source of axions as well as different velocity distribution compared with those in the dark matter halo 51 . In this work, however, we only consider the axion wind from the earth's movement through the dark matter halo which gives the following parameters 25 :…”
Section: Axion Windmentioning
confidence: 99%
“…The most exploited detection principle of axions and ALPs is the haloscope proposed by Sikivie [14,15], whose description is addressed in a review: [16]. Examples of running experiments, also shown by the vertical lines in Figure 1, are ADMX [17,18], HAYSTAC [19], CAPP-8T [20], CAPP-9T [21], ORGAN [22], and QUAX [23][24][25][26]; other proposed experiments include RADES [27,28], MADMAX [29], BRASS [30], and KLASH [31][32][33].…”
Section: Introduction 1detection Of Axionsmentioning
confidence: 99%
“…Applications of such systems range from quantum information processing [1][2][3] and coherent conversion of microwave to optical frequency light [4,5], to microwave components in the form of filters, circulators, isolators and oscillators. Additionally, such systems are used in the study of hybrid quantum systems [6,7], Quantum electrodynamics (QED) [8][9][10], and direct detection of dark matter [11][12][13][14][15]. In the context of dark matter detection, it has been shown that strongly coupled cavity-magnon systems are useful for expanding the range of detectable dark matter masses [11].…”
Section: Introductionmentioning
confidence: 99%